Pro SQL Server 2008 Replication - Paul, Sujoy (Apress : Imprint: Apress, 2009)
Pro SQL Server 2008 Replication is for Microsoft database developers and administrators who want to learn about the different types of replication and those best suited to SQL Server 2008. This book will also cover advanced topics like replication with heterogeneous databases, backup and recovery of replicated databases, database mirroring with replication, log shipping with replication, troubleshooting, plus optimization and tuning. Tools like tablediff, SQLCMD, DTA, SQL Profiler, and Replication Monitor will be discussed to demonstrate the different techniques used in monitoring, administering, and troubleshooting replication. Examines the detailed configuration and the internal workings of the different replication types using real-life scenarios Covers replication with database mirroring and troubleshooting Discusses replication administration using different tools.